First Reported Case of Isolated Persistent Genital Arousal Disorder in a Male - Bradford J. Stevenson; Tobias S. Köhler (Case Reports in Urology)
Introduction. Persistent genital arousal disorder (PGAD) is a newly recognized disorder in women. It is described as unwanted, persistent feelings of genital arousal unrelated to sexual desire and not relieved by orgasm. Its prevalence is estimated to approach 1% of young women. Until now, this has not been described in men. Aim. Here we present a case of a 27-year-old male with symptoms consistent with PGAD and describe successful treatment. Methods. A 27-year-old male presented to urology clinic with the chief complain of persistent feelings of impending orgasm. He reported a sensation similar, but not identical, to sexual arousal that did not occur in the setting of sexual thoughts or desire. Orgasm alleviated the arousal for only a short time after which the symptoms would return. This had become quite bothersome to him. Results. After assessing for a neurological cause and finding none, the patient was started on paroxetine daily with complete resolution of symptoms. Conclusions. PGAD is a disorder previously described only in females. Although symptoms of PGAD have been described in a male as part of another disorder complex, this report describes the first reported isolated case in a male and the successful treatment.